Promising Practices and Emerging Ideas in Academic Integrity Policy Development - Ives, Cindy; Kier, Cheryl A (Canadian Perspectives on Academic Integrity, 2021)
Recently, Athabasca University canvassed faculty, tutors, and students about their perspectives on academic integrity. Responses to open-ended questions were received from 102 faculty and tutors and 146 students, generating hundreds of comments. The survey asked how Athabasca University could improve its policies concerning issues of academic integrity, about satisfaction with how academic violations were treated, on the role of faculty and tutors in encouraging academic integrity, and on how faculty and tutors handled cases of misconduct. As well, we collected suggestions from faculty, tutors, and students for reducing cheating, increasing academic integrity, and other ideas about academic integrity in general. Using content analysis, we categorized these open-ended replies into similar threads. Five general recommendation groupings were extracted: policy and procedures, compliance and commitment, resources, plagiarism detection software, and other. The proposed presentation will focus on two sets of recommendations: policy and procedures and plagiarism detection software. We believe that our work meets the criteria for the call for papers because we are learning from our faculty, tutors and students and are interested in sharing their insights. Although we conducted the study pre-COVID-19, we think the recommendations apply now as much as they did then, and will continue to be useful into the future.